Effect of Thermal Treatment on Kelulut Honey Towards the Physicochemical, Antioxidant and Antimicrobial Properties - MARDHIAH, MOHD SHAHABUDDIN; MOHD ALHAFIIZH, ZAILANI; WAN ROSLINA, WAN YUSOF; NOORASMIN, MOKHTAR AHMAD (UNIMAS Publisher, 2022)
Heat treatment on commercial honey could deteriorate its quality associated with physicochemical and bioactive capacities. In this study, the effects of thermal treatment (50 °C, 75 °C and 90 °C) on the physicochemical properties (i.e., pH, colour intensity), total phenolic content and total flavonoid content were investigated on the Kelulut honey. The results revealed a significant increase in TFC (0.154 mg QE/g honey) for the heat-treated Kelulut honey compared to the control (0.085 mg QE/g honey). The antioxidant activity of the heat-treated honey revealed an increase in 2, 2- Diphenyl-1-picrylhydrazyl levels by 42%, while the ferric reducing antioxidant power levels were reduced significantly by 22.4% compared to the untreated honey. The antimicrobial activities of heattreated honey declined against Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Salmonella typhi bacteria at 75 °C and 90 °C. Based on the effects observed in the bioactive capacities of the heat-treated honey, it is therefore recommended to minimize thermal treatment on the honey during the processing to maintain its natural nutritional quality and benefit consumers.